Comorbid depressive disorders and left‐side dominant occlusal discomfort in patients with phantom bite syndrome. (28th August 2019) - Shinohara, Yukiko; Umezaki, Yojiro; Minami, Ichiro; Watanabe, Motoko; Miura, Anna; Mikutsuki, Lou; Kawasaki, Kaoru; Sugawara, Shiori; Trang, Tu Thi Hyen; Suga, Takayuki; Watanabe, Takeshi; Yoshikawa, Tatsuya; et al.
Abstract: Background: Phantom bite syndrome (PBS) is characterised by occlusal discomfort without corresponding dental abnormalities. Despite repeated, failed dental treatments, patients with PBS persist in seeking bite correction. PBS has been regarded as a mental disorder. However, we have reported that PBS patients with a dental trigger tend to have less psychiatric history than those without. Hence, the symptoms of PBS cannot be explained by a mental disorder alone, and it is unclear if mental disorders affect occlusal sensation. Objective: To elucidate the pathophysiology of PBS, we analysed the dental history, PBS symptom laterality and psychiatric history of patients. Methods: In this retrospective study, we reviewed outpatients with PBS who presented at our clinic between April 2012 and March 2017. Their medical records were reviewed for demographic data, medical history and laterality of occlusal discomfort. Results: Approximately half of the 199 enrolled patients had bilateral occlusal discomfort. In the others, the side with occlusal discomfort generally tended to be the one that had received dental treatment. There was no significant relationship between the side chiefly affected by occlusal discomfort and whether dental treatment had been received; however, the affected side differed depending on whether the patient had comorbid psychiatric disorders ( P  = .041). Conclusions: The distributions of the side with symptoms of PBS were different between those with and without comorbid psychiatric disorders, suggesting that psychiatric disorders might affect occlusal sensation due to a subtle dysfunction in brain areas central to sensory integration. Central dysfunction might play an important role in PBS.